2021
DOI: 10.4028/www.scientific.net/kem.892.81
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hardness and Microstructure of Cast Wheel and Spoke Wheel Rims of Motorcycles Made of Aluminum Alloy Alloy

Abstract: The rim is one of the main components in a motorized vehicle system, both two and three wheels. Rim loads when used are dynamic and often even shock. This study aims to study the mechanical characteristics, especially the hardness properties of spoke wheel rims and cast wheel rims made of aluminum alloy used in motorcycles and compare the results. Hardness testing is carried out on the spoke wheel and cast wheel specimens, using the Rockwell method with an identifier of 1/16 ball and a spectrometer used for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Husaini et al found that the cast wheel rims can withstand a load of 3 tons (30000 N), and the value of rim tension can be accepted until the fracture is 45.84MPa. Meanwhile, spoke wheel rims can withstand smaller compressive loads than cast wheel rims, which are 2 tons (20000 N), and the rims can accept the stress of 66.04MPa until they break [6]. Casting wheels are made by pouring molten metal into a mold and then allowing it to cool and solidify.…”
Section: Manufacturing Processmentioning
confidence: 99%
“…Husaini et al found that the cast wheel rims can withstand a load of 3 tons (30000 N), and the value of rim tension can be accepted until the fracture is 45.84MPa. Meanwhile, spoke wheel rims can withstand smaller compressive loads than cast wheel rims, which are 2 tons (20000 N), and the rims can accept the stress of 66.04MPa until they break [6]. Casting wheels are made by pouring molten metal into a mold and then allowing it to cool and solidify.…”
Section: Manufacturing Processmentioning
confidence: 99%